Cystic spermatogenesis in three species of the prolixus complex (Hemiptera: Triatominae) - Alevi, K. C. C. [UNESP]; Castro, N. F. C. [UNESP]; Oliveira, J. [UNESP]; Rosa, J. A. [UNESP]; Azeredo-Oliveira, M. T. V. [UNESP] (Taylor &francis Ltd, 2015)
The reproductive biology of triatomines and, more specifically, the general aspects of spermatogenesis and spermiogenesis are well known. However, reported structural analyses of the testicles are restricted to the genus Triatoma. Thus, this paper describes the spermatogenesis of three species of the genus Rhodnius (R. neglectus, R. prolixus and R. robustus), by means of structural analysis. The general analysis of semi-thin sections of testicular follicles of R. prolixus, R. robustus and R. neglectus revealed that spermatogenesis is cystic in these species. Furthermore, the structural analysis of the spermatogenesis of R. prolixus (Colombia and Costa Rica), R. robustus and R. neglectus showed stages of spermatogenesis. In this paper, the analysis of spermatogenesis of three Rhodnius species shed light on this cystic spermatogenesis phenomenon; no intraespecific differences were observed among R. prolixus from different countries. Thus, although new structural analyses in other genera of the subfamily Triatominae should be performed, this paper describes cystic spermatogenesis in three species of the genus Rhodnius. These results contribute to the knowledge of the class Insecta and allow for a more detailed study of the reproductive biology of these important vectors of Chagas disease.
Keywords: Triatominae subfamily; spermatogenesis; structural analyses; Tribe Rhodniini